Strategi Pengelolaan Informasi Instagram @kabupaten.bogor dalam Meraih Predikat 1 Media Sosial Terbaik Humas Jabar Awards 2023. - Parsono, Slamet; Safa Maura, Latisya (JURNAL KOMUNIKATIO, 2024)
The Bogor Regency Government has a central role in information management strategies to establish communication with the public. Instagram is one of the most effective social media for Bogor Regency Government Public Relations in disseminating information. The purpose of this research is to find out how the Bogor Regency Government's Public Relations strategy won the title of 1 Best Social Media PR Jabar Awards 2023. Researchers used four stages (4C) of social media management from Chris Heuer (2010), namely (1) context or creating messages; (2) communication or delivering messages; (3) collaboration or cooperation; and (4) connection or maintaining good relations. This research method uses a qualitative approach through data collection of observation, interviews, and documentation. Based on the results of the study, Bogor Regency Public Relations has succeeded in managing information through Instagram so that it can win the title of 1 Best Social Media Public Relations Jabar Awards 2023. Public Relations of Bogor Regency Government is very active in producing planned and measured messages by maximizing the features on Instagram social media.